On Robust Design in the Conceptual Design Phase - A Qualitative Approach and A Semi-Analytic Approach to Robust Design in the Conceptual Design Phase - Andersson, Peder (My University, 1995)
One of the most important contributions to quality engineering over the last decades is the concept of robust design and its accomplishment through the use of various experimental methods. However, the prerequisite parameter design in terms of a robust solution principle are seldom discussed and methods that aid robust design in the conceptual design phase are, to our knowledge, few. This article forwards the suggestion to use the principles behind the error transmission formula as a semi-analytic method for evaluation of robustness of concept solutions, prior to entering Taguchi's parameter design stage.